L’ Art rhétorique d’Aristote, une oeuvre pour notre temps? - Motte, André (Wydawnictwo Naukowe Instytutu Filozofii UAM, 2012)
Having discussed some political and philosophical stakes of the Greeks’ invention of the rhetorical art, the present research aims to show the great originality of Aristotle’s treatise in comparison to his precursors. Subsequently, the article illustrates the amazing scientific relevance of Aristotle’s work for the French‑speaking world in the past half a century. Finally, the paper poses the question whether its underlying concepts can nowadays be of any significance from a practical point of view.
Keywords: Aristotle; Rhetoric